Selenate and molybdate alter sulfate transport and assimilation in Brassica juncea L. Czern: implications for phytoremediation - Schiavon, Michela; Wirtz, Markus; Hell, Rüdiger (Environmental and experimental botany, 2012)
The interaction of selenate and molybdate with the transport and assimilation of sulfate, and the effect of S on Se and Mo accumulation were investigated in Brassica juncea. Plants were supplied with different combinations of S and Se, or S and Mo for 24h, and selenate and molybdate were given to plants at concentrations (200μM) equal to that of sulfate in the S-sufficient condition. Se and Mo significantly reduced the plant growth. In S-sufficient plants, Se and Mo decreased sulfate uptake rate (at 24h), and Se repressed the expression of the sulfate transporter BjSultr2.1. This effect was different from the one we observed for sulfate, which rapidly inhibited the sulfate uptake rates in +S plants. In S-starved plants, Se, Mo and S repressed sulfate uptake immediately (after 10min), and the concomitant down-regulation of BjSultr2.1 occurred only in roots of plants treated with S. In plants exposed to Se or Mo the root expression of BjSultr2.1 was repressed later, after 6h. S-starved plants accumulated significantly more Se and Mo than S-sufficient plants, likely due to the lack of competition of molybdate or selenate with sulfate for the transport through the same carriers. The up-regulation of the molybdenum transporter (MOT1) gene expression could explain the higher amount of Mo than Se measured in the plant tissues. Se and Mo reduced the levels of cysteine (Cys) and glutathione (GSH) in +S plants, but increased the amount of these non-protein thiols in −S plants. The increase of GSH content in −S+Se plants was likely responsible for the down-regulation of the selenium binding protein (SBP1) gene, while the induction of SBP1 observed in +S plants was mainly due to Se toxicity. The up-regulation of SBP1 was also evidenced in plants exposed to Mo, regardless of S availability and GSH content. Our results give better insight into plant uptake mechanisms for Se and Mo, and also have implications for phytoremediation. The interactions between sulfate and selenate or molybdate must be carefully considered when plants are employed for the remediation of Se- or Mo-contaminated sites, as the accumulation of the two contaminants in plants might be altered by the sulfate concentration in the growing medium.
Gesehen am 03.05.2018